Efficiency of blind source separation in a real room - Libiszewski, Paweł; Kociński, Jędrzej (Archives of Acoustics, 2007)
The present study is concerned with the effectiveness of the blind source separation (BSS)in real acoustical environment measured by means of a speech reception threshold, SRT. BSSis a multisensoral method that leads to a signal extraction from a mixture of sounds. The performanceof such algorithms are most often described by means of the increase in signal-tonoiseratio, SNR. However, the SNR is not an appropriate measure for speech enhancement,since the increase in SNR does not lead directly to the improvement of the speech intelligibility.Thus, the relationship between an increase in SNR and speech intelligibility is notstraightforward.This work shows some experiments in which the speech masked by a babble noise, musicor concurrent speech was separated out using an algorithm for convolutive BSS. The SRT beforeand after the separation was measured for subjects with audiologically normal hearing.All recordings were carried out in a small office room using an array of two microphones.Two spatially separated loudspeakers were used as sources of signals: target speech and disturbances.The results of the experiment revealed a marked improvement in the speech intelligibility:the decrease in SRT reached about 7 to 24 dB in individual cases.